Optimization of the Use of Medical Equipment as an Effort to Increase the Efficiency and Accuracy OF Doctors' Work in the Operating Room at Hastien Rengasdengklok Hospital - Christian Sumilat; Dicky Yulius Pangkey; Tinon Ambarini (Research of Service Administration Health and Sains Healthys, 2025)
The optimization of medical device utilization in hospitals is often hindered by limited medical staff training, unintegrated equipment management, and inadequate infrastructure. These factors contribute to low efficiency in doctors' performance and declining quality of healthcare services. This study aims to explore hospital strategies for optimizing the use of medical devices in operating rooms and to understand doctors' perceptions of their effectiveness. The qualitative study was conducted at Hastien Rengasdengklok Hospital over one month starting June 1, 2025. Data were collected through in-depth interviews, observations, and documentation involving the hospital director, management, specialists, nurses, and patients. Validity was maintained through triangulation and member checks, while research ethics were upheld through confidentiality and informed consent. The hospital's optimization strategy includes regular training, equipment maintenance, SOP standardization, and cross-professional collaboration, reflecting a comprehensive managerial transformation based on technical, ethical, and epistemological approaches. This strategy aligns with the Utilization Management and Technology Acceptance Model theories. However, challenges such as substandard equipment and uneven training remain. The hospital responds with innovations like hybrid training and digital technology integration. Doctors perceive medical devices as essential tools that extend their professional responsibility and are viewed as strategic assets in line with the Resource-Based View approach. These perceptions, rooted in direct experience, support the principles of Total Quality Management and foster a learning organizational culture focused on delivering high-quality and sustainable services.